Efficacy and safety of faricimab for neovascular age-related macular degeneration: a systematic review and network meta-analysis - Francisco Rodríguez; Daniel Samacá-Samacá; Claudia Hernández-Castillo; Laura Prieto-Pinto; Carolina Sardi; Hugo Ocampo; Joshua Kock; Fabián Hernández (BMJ Open Ophthalmology)
Objective To evaluate the efficacy and safety of faricimab compared with other anti-vascular endothelial growth factor (anti-VEGF) agents in treating neovascular age-related macular degeneration (nAMD) patients.Methods and analysis A systematic review (SR) was conducted up to January 2023. Network meta-analyses (NMA) were performed, including sensitivity and subgroup analyses for naïve population. Outcomes included changes in visual acuity (Early Treatment of Diabetic Retinopathy Study [ETDRS] letters), anatomical changes, frequency of injections and adverse events. The Cochrane Collaboration guidelines and the Confidence in Network Meta-Analysis framework were used for the SR and the certainty of evidence, respectively.Results From 4128 identified records through electronic databases and complementary searches, 63 randomised controlled trials (RCTs) met the eligibility criteria, with 42 included in the NMA. Faricimab showed a significant reduction in the number of annual injections compared with most fixed and flexible anti-VEGF treatment regimens, while showing no statistically significant differences in visual acuity through ETDRS letter gain, demonstrating a comparable efficacy. Retinal thickness results showed comparable efficacy to other anti-VEGF agents, and inferior only to brolucizumab. Results also showed that more patients treated with faricimab were free from post-treatment retinal fluid compared with aflibercept every 8 weeks, and both ranibizumab and bevacizumab, in the fixed and pro re nata (PRN) assessed schedules. Faricimab showed a comparable safety profile regarding the risk of ocular adverse events and serious ocular adverse events (SOAE), except for the comparison with brolucizumab quarterly, in which faricimab showed a significant reduction for SOAE risk.Conclusion Faricimab showed a comparable clinical benefit in efficacy and safety outcomes, with a reduction in annual injections compared with fixed and flexible anti-VEGF drug regimens, representing a valuable treatment option for nAMD patients.PROSPERO registration number CRD42023394226.